Midwifery Job Autonomy in New Zealand: I do it all the time. Issue 1 (February 2021) - Clemons, Janine H.; Gilkison, Andrea; Mharapara, Tago L.; Dixon, Lesley; McAra-Couper, Judith
Abstract: Introduction: This research aimed to identify what supports and what hinders job autonomy for midwives in New Zealand. Methods: Registered midwives participated in an open-ended, online survey in 2019. Anonymised participants were asked to describe an incident when they felt they were using their professional judgement and/or initiative to make decisions and the resultant actions. The data was analysed thematically. Findings: The participants identified that autonomy is embedded within midwifery practice in New Zealand. Self-employed midwives who provide continuity of care as Lead Maternity Carers, identified they practice autonomously 'all the time'. The relationship with women and their family, and informed decision making, motivated the midwife to advocate for the woman – regardless of the midwife's work setting. Midwifery expertise, skills, and knowledge were intrinsic to autonomy. Collegial relationships could support or hinder the midwives' autonomy while a negative hospital work culture could hinder job autonomy. Discussion: Midwives identified that autonomous practice is embedded in their day to day work. It strengthens and is strengthened by their relationships with the woman/whanau and when their body of knowledge is acknowledged by their colleagues. Job autonomy was described when midwifery decisions were challenged by health professionals in hospital settings and these challenges could be viewed as obstructing job autonomy. Conclusion: The high job autonomy that New Zealand midwives enjoy is supported by their expertise, the women and colleagues that understand and respect their scope of practice. When their autonomy is hindered by institutional culture and professional differences provision of woman-centred care can suffer.